Natural Silk Agribusiness Development Strategy in South Sulawesi Province, Indonesia - Ashar, Nurul Magfirah; Nurmalina, Rita; Muflikh, Yanti Nuraeni (Universitas Panji Sakti, 2024)
Natural silk is an agribusiness activity consisting of interconnected and interrelated upstream-to-downstream subsystems. It is one of the leading industries in South Sulawesi Province, the national silk-producing region. The government has launched various development programs and policies to increase natural silk production in South Sulawesi Province but has not achieved the expected targets. Therefore, this research analyzed natural silk agribusiness's internal and external environment to formulate alternative and development strategy priorities. The research was conducted in South Sulawesi Province, with a regional focus on Soppeng Regency and Wajo Regency in February – April 2024. The location selection was carried out by purposive sampling, considering that the area is the main priority in developing natural silk in South Sulawesi Province. The selection of respondents used a deterministic approach in the form of purposive sampling, with 41 respondents in the study. Eight experts filling out a pair comparison questionnaire determined the strategy's priority. The research method used is A'WOT Analysis. The research results show that eight alternative strategies were formulated. The main priority is optimizing policies and regulations from departments/agencies related to the development of natural silk, with a weight value of 0.160. It is hoped that all the results of formulating alternative strategies can be considered in developing natural silk agribusiness in South Sulawesi Province.